Incidence, risk factors, and thrombotic load of pulmonary embolism in patients hospitalized for COVID-19 infection. Issue 2 (February 2021) - García-Ortega, Alberto; Oscullo, Grace; Calvillo, Pilar; López-Reyes, Raquel; Méndez, Raúl; Gómez-Olivas, José Daniel; Bekki, Amina; Fonfría, Carles; Trilles-Olaso, Laura; Zaldívar, Enrique; Ferrando, Ana; Anguera, Gabriel; et al.
Summary: Objective: To determine the incidence, characteristics, and risk factors of pulmonary embolism (PE) among patients hospitalized for COVID-19. Patients and Methods: We performed a prospective observational study of a randomly selected cohort of consecutive patients hospitalized for COVID-19 infection between March 8, 2020 through April 25, 2020. All eligible patients underwent a computed tomography pulmonary angiography independently of their PE clinical suspicion and were pre-screened for a baseline elevated D-dimer level. Results: 119 patients were randomly selected from the 372 admitted to one tertiary hospital in Valencia (Spain) for COVID-19 infection during the period of study. Seventy-three patients fulfilled both the inclusion criteria and none of the exclusion criteria and were finally included in the study. Despite a high level of pharmacological thromboprophylaxis (89%), the incidence of PE was 35.6% (95% confidence interval [CI], 29.6 to 41.6%), mostly with a peripheral location and low thrombotic load (Qanadli score 18.5%). Multivariate analysis showed that heart rate (Hazard Ratio [HR], 1.04), room-air oxygen saturation (spO2) (HR, 0.87), D-dimer (HR, 1.02), and C-reactive protein (CRP) levels (HR, 1.01) at the time of admission were independent predictors of incident PE during hospitalization. A risk score was constructed with these four variables showing a high predictive value of incident PE (AUC-ROC: 0.86; 95% CI: 0.80 to 0.93). Conclusions: Our findings confirmed a high incidence of PE in hospitalized COVID-19 patients. Heart rate, spO2, D-dimer, and CRP levels at admission were associated with higher rates of PE during hospitalization.